Primary tumor volume as a predictor of distant metastases and survival in patients with sinonasal mucosal melanoma. Issue 11 (1st August 2020) - Flukes, Stephanie; Lohia, Shivangi; Barker, Christopher A.; Cracchiolo, Jennifer R.; Ganly, Ian; Patel, Snehal G.; Roman, Benjamin R.; Shah, Jatin P.; Shoushtari, Alexander N.; Tabar, Viviane; Shah, Akash; Cohen, Marc A.
Abstract: Background: Sinonasal mucosal melanoma (SNMM) is an aggressive cancer with high mortality. Identifying patients at risk of distant metastasis assists with management and prognostication. We aimed to define the relationship between volume, survival, and risk of distant metastases. Methods: A retrospective review of all patients with SNMM treated at a single institution over a 21‐year period was conducted. Tumor volume was calculated using cross‐sectional imaging and survival analysis was performed. Results: Sixty‐one patients were included. Tumor volume was predictive of local progression‐free survival ( P = .03), distant metastases‐free survival (DMFS) ( P = .002), and overall survival (OS) ( P = .02). It was a better predictor than AJCC stage and T‐classification. Tumor volume equal to or greater than 5 cm 3 was associated with a significantly worse DMFS and OS ( P = .02 and .009, respectively). Conclusion: Calculation of tumor volume assists in quantifying the risk of distant metastases and death in SNMM.